An Impedimetric‐Fluorescence Double‐Checking Biosensor with Enhanced Reliability Based on Graphene Oxide. Issue 14 (27th July 2015) - Li, Aixue; Zhang, Jian; Yu, Xin; Li, Jianhua; Qiu, Jichuan; Zhao, Zhenhuan; Guo, Weibo; Claverie, Jerome P.; Mou, Xiaoning; Liu, Hong
<x xml:space="preserve">Abstract</x> MicroRNA (miRNA) is a class of clinically significant diagnostic and prognostic markers for some diseases, especially for cancer. Graphene oxide (GO) has been reported to bind and quench dye‐labeled single‐stranded DNA (ssDNA) probes while it has less affinity toward double‐stranded DNA (dsDNA) or hybrids of DNA/RNA. This property makes it very suitable to construct a double‐checking system for miRNA detection, thus increasing the reliability of detection. This kind of double‐checking sensor will have great potential in clinical diagnosis. Based on this concept, in this study a simple and sensitive electrochemical impedance spectroscopy biosensor for miRNA‐21 is developed using a GO‐coated electrode. Simultaneously, the fluorescence of the remaining hybridization solution which contains dissociated duplex of ssDNA/miRNA is also investigated to double check the signal and increase its reliability. Therefore, a GO‐based double‐checking biosensor is developed for miRNA‐21 detection, which shows simplicity, high sensitivity and selectivity, and outstanding reliability. This is the first time to integrate the electrochemical impedimetric method and fluorescence method in one sensing system for detecting miRNA based on GO. It is believed that this work will have a profound impact on the design of graphene‐based biosensors for miRNA detection.